2010
DOI: 10.1016/j.micpath.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilum APH_0032 is expressed late during infection and localizes to the pathogen-occupied vacuolar membrane

Abstract: Anaplasma phagocytophilum infects neutrophils and myeloid, endothelial, and tick cell lines to reside within a host cell-derived vacuole that is indispensible for its survival. Here, we identify APH_0032 as an Anaplasma-derived protein that associates with the A. phagocytophilumoccupied vacuolar membrane (AVM). APH_0032 is a 66.1 kDa acidic protein that electrophoretically migrates with an apparent molecular weight of 130 kDa. It contains a predicted transmembrane domain and tandemly arranged direct repeats th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 55 publications
5
94
0
Order By: Relevance
“…A search against the Pfam domain database revealed that, as expected, all AnkA sequences detected during the present study contained ankyrin repeats. Furthermore, all of them showed a putative T4SS signal sequence (51) in line with the fact that AnkA is translocated by heterologous T4SSs (29,34). AnkA sequences of all four clusters contained at their C-terminal end several tyrosine kinase phosphorylation sites predicted by Scansite (http: //scansite.mit.edu/).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…A search against the Pfam domain database revealed that, as expected, all AnkA sequences detected during the present study contained ankyrin repeats. Furthermore, all of them showed a putative T4SS signal sequence (51) in line with the fact that AnkA is translocated by heterologous T4SSs (29,34). AnkA sequences of all four clusters contained at their C-terminal end several tyrosine kinase phosphorylation sites predicted by Scansite (http: //scansite.mit.edu/).…”
Section: Resultsmentioning
confidence: 62%
“…Although the exact function of AnkA has not been determined yet (50), its C-terminal end has been shown to be secreted by the VirB/ VirD4-dependent type IV secretion system (T4SS) of Agrobacterium tumefaciens (34) and the Dot/Icm type T4SS of Legionella pneumophila (29). After translocation, AnkA is tyrosine phosphorylated by the host cell tyrosine kinases Src (31) and Abl (34).…”
mentioning
confidence: 99%
“…L. pneumophila has been invaluable in identifying C. burnetii T4SS substrates (35,48,67). However, direct demonstration of effector secretion by C. burnetii would be ideal.…”
Section: Resultsmentioning
confidence: 99%
“…We detected expression of 27 hypothetical proteins in tick salivary glands by proteomics or RNA-seq (Table 3 and Table 4). Some of these proteins have previously been characterized in HL-60 cultures for their roles in A. phagocytophilum infection (14,15,34) or identified as immunoreactive proteins (24). Two hypothetical proteins, APH_0220 and APH_0792, were classified as among the most abundant in the HL-60 culture proteome (23).…”
Section: Resultsmentioning
confidence: 99%